Review of four species of the genus Brachinus Weber (Coleoptera: Caraboidea: Brachinidae) from the Philippines - Tian, Mingyi; Deuve, Thierry (Zootaxa, 2007)
Species diversity of the bombardier beetles is poorly known in Asia except Japan. In the present paper, species of the genus Brachinus Weber of the Philippines are dealt with. Among the four species reported in the Philippines, two species are described as new to science: B. philippinensis Tian & Deuve, new species and B. solidipalpis Tian & Deuve, new species. Redescriptions are given for the two known species, B. luzonicus Chaudoir and B. piceus Chaudoir. A key to all Philippine species of Brachinus is provided.